A novel composite interlayer assembled for C/SiC-GH99 brazed joints. (February 2019) - Yang, J.H.; Zhang, L.X.; Sun, Z.; Feng, J.C.
Highlights: A novel composite interlayer was designed by Ti-40Ni-20Nb/Nb/Ni-19Cr-10Si, with which C/SiC composite and GH99 alloy were successfully brazed at 1200 °C for 20 min. The interfacial microstructure of the joint was characterized and the effects of the Nb foil thickness on the microstructure and shear strength of the joint were investigated. The composite interlayer could inhibit the diffusion of Ni to the C/SiC composite and optimize the interfacial microstructure adjacent to the C/SiC composite significantly. The shear strength was 123 MPa at room temperature, 88 MPa at 400 °C, 75 MPa at 600 °C and 57 MPa at 800 °C, respectively. Abstract: A novel composite interlayer composed of Ti-40Ni-20Nb/Nb/Ni-19Cr-10Si was designed. By using that, a reliable C/SiC-GH99 brazed joint was successfully obtained at 1200 °C for 20 min. Results demonstrated that the composite interlayer could relieve the residual stress. Practically, the diffusion of Ni was drastic inhibited at the GH99 side. The formation of brittle Ni-Si intermetallics at the C/SiC side was thus greatly decreased. The effects of the Nb foil thickness in the composite interlayer on the interfacial microstructure were studied. When the original thickness of the Nb foil was larger than 100 μm, the residual Nb foil could inhibit the diffusion of Ni and optimize the interfacial microstructure. A desirable interfacial microstructure composed of (Ti, Nb)Ni, (Ti, Nb)C and NiNbSi was obtained. The optimal shear strength at room temperature was 123 MPa. The high temperature shear strength was 88 MPa, 75 MPa and 57 MPa at 400 °C, 600 °C and 800 °C, respectively.